Penerapan Problem Based Learning Berbantuan Geoboard untuk Meningkatkan Pemahaman Konsep Siswa pada Materi Kekongruenan - Sadaria; Baharuddin; Rosdiana (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study is a pre-experimental research that aims to investigate: (1) students’ conceptual understanding ability after the implementation of Problem Based Learning assisted by a geoboard, and (2) whether the implementation of Problem Based Learning assisted by a geoboard has an effect on students’ conceptual understanding ability in congruence material. Data were obtained from observations and tests. The data were analyzed using statistics. The results show that the implementation of Problem Based Learning assisted by a geoboard has an effect on students’ conceptual understanding ability in congruence material, with an effect size of 0.667, which falls into the medium category.